Studi Kajian Peluang Bisnis pada Jasa Pembuatan Undangan dan Mahar untuk Pengantin - Br. Sembiring, Celly Shetyana; Purba, Faradiba Ulfa; Putri, Melva Adelia; Butar-Butar, Nunut Syahputra; Rangkuty, Dewi Mahrani (Universitas 17 Agustus 1945 Semarang, 2022)
This study discusses the business opportunities of the creative sector assessing the many needs of the community for invitation making services and accompanying equipment in a solemn event in the form of a wedding. This paper examines how human creativity is one of the causes of the creation of a business opportunity. In fact, creativity itself can create a business. In the face of a situation that requires humans to be able to meet their needs, human creativity by looking at the available business opportunities, in our discussion we see from business opportunities that creative idea services are needed to create a good impression through wedding invitations and bridal dowries in weddings. From the analysis described, this type of invitation and dowry service business will not be extinct by time, a promising type of business because every wedding requires invitations and dowries. This business requires promotion which can be done in several ways such as participating in Wedding exhibitions or utilising social media to increase revenue and to be better known by the public.